Fingerprint analysis of FTIR spectra of polymers containing vinyl acetate - Ramírez Hernández, Aurelio; Aguilar Flores, Celia; Aparicio Saguilan, Alejandro (DYNA, 2019)
The analysis of materials using Fourier transform infrared (FTIR) spectroscopy has a unique area called the fingerprint region for each compound. However, this area is almost never discussed because of its complexity due to the large number of signals that appear in it. In this work, the fingerprint region analysis of the ethylene–vinyl acetate copolymer (EVA) with different percentages of vinyl acetate (VA) (18%, 28%, 40%) was performed. In comparison with other instrumental techniques, the crystallinity and structural arrangement of the EVA copolymers were determined simply and economically. The crystallinities for EVA18, EVA28 and EVA40 were 24.39%, 6.95% and1.03%, respectively. In terms of structural ordering, the number of linear chains of EVA copolymer decreases as the concentration of VA increases, which favors the reduction of degrees of freedom and the formation of hydrogen bonds.
Análisis en la huella dactilar de espectros FTIR de polímeros que contienen etileno
Keywords: Vibración; Intensidad; Sobrelapadas